UJI TOKSISITAS EKSTRAK ETANOL KAYU CEREMAI (Phyllanthus acidus L) TERHADAP LARVA UDANG Artemia salina DENGAN METODE BRINE SHRIMP LETHALITY TEST (BST) - Desi Kusumawati (Universitas PGRI Madiun, 2018)
The use of Otaheite gooseberry wood as a traditional medicine needs to be supported by scientific information about the efficacy and side effect. The objective of this research is to prove the presence of toxicity potency in ethanol extract of otaheite gooseberry wood using BST methods. An experimental research. Total sampel were 160 Brine shrimp (Artemia salina Leach) larvae. Ten larvae used in each 6 groups with 3 times replication. Each group was consecutively given 500 μg/ml, 300 μg/ml, 200 μg/ml, 100 μg/ml, 50 μg/ml, 0 μg/ml concentrate of ethanol extract of otaheite gooseberry wood, the sixth group was used as control. Data obtained by calculating amount of died larva in 24 hours after treatment. LC50 value was analyzed by probit analysis using SPSS 16.0 for windows,. Presumable compound contained in extract etanol Otaheite gooseberry wood in which have tokcixity testcase by “skrining fitokimia”. The average mortality of larvae at a concentration of 500, 300, 200, 100, 50, and 0 μg/ml consecutively were 9,33; 7,33; 4,67; 3,33; 2 and 0. The higher the extract concentration led to a growing number of high larval mortality. LC50 value of fruit extract of otaheite gooseberry wood was 275,035μg/ml. LC50 <1000 μg/ml indicates ethanol extract of otaheite gooseberry wood own a potential toxicity to larvae of Artemia salina Leach.